2018
DOI: 10.1038/s41419-018-0641-7
|View full text |Cite
|
Sign up to set email alerts
|

Hirsutine induces mPTP-dependent apoptosis through ROCK1/PTEN/PI3K/GSK3β pathway in human lung cancer cells

Abstract: Hirsutine extracted from Uncaria rhynchophylla has been shown to exhibit anti-cancer activity. However, the molecular mechanism by which hirsutine exhibits anti-lung cancer activity remains unclear. In the present study, we showed that hirsutine induces apoptosis in human lung cancer cells via loss of mitochondrial membrane potential (∆ψm), adenosine triphosphate (ATP) depletion, ROS production, as well as cytochrome c release. Dephosphorylation of GSK3β is involved in hirsutine-mediated mitochondrial permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 53 publications
3
51
0
Order By: Relevance
“…Several researches have demonstrated that the activation of ROCK1 could activate PTEN, further inactivate PI3K/AKT, subsequently leading in turn to GSK‐3β dephosphorylation and mPTP opening, and we found that GAS5 could positively regulate ROCK1. Therefore, whether GAS5 regulates PTEN/PI3K/AKT/GSK‐3β/mPTP signal axis was further explored.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Several researches have demonstrated that the activation of ROCK1 could activate PTEN, further inactivate PI3K/AKT, subsequently leading in turn to GSK‐3β dephosphorylation and mPTP opening, and we found that GAS5 could positively regulate ROCK1. Therefore, whether GAS5 regulates PTEN/PI3K/AKT/GSK‐3β/mPTP signal axis was further explored.…”
Section: Resultsmentioning
confidence: 58%
“…For instance, once mPTP opens, cytochrome c will be driven from the mitochondria into the cytoplasm, then caspases cascades are activated, and ultimately cell apoptosis will occur . GSK‐3β, a key upstream regulator of mPTP opening, is typically regulated by the PI3K/AKT‐mediated phosphorylation . mPTP opening will decrease, once GSK‐3β at Ser9 cite is phosphorylated .…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, ROCK1 promotes mitochondrial dysfunction and mitochondria-related apoptosis through the PTEN pathway and PI3K/Akt pathway in human leukemia cells. 50 In this study, we can be certain that miR-31 is the upstream effector of ROCK1/F-actin axis, and inhibiting the ROCK1/F-actin pathway abolishes the beneficial effects of miR-31 on viability, mitochondrial function, proliferation, and movement in liver cancer HepG2 cells. However, the targets of miR-31 are not clearly described in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Growing evidence has demonstrated that active Akt promotes survival of cardiomyocytes in vitro and protects against MIRI [18]. Gsk-3β, a crucial downstream molecule of PI3K/Akt signal pathway, typically regulated mPTP opening by PI3K/Akt-mediated phosphorylation [19]. Several studies have reported that ischemic preconditioning [20] or postconditioning [21] could prevent MIRI through activation of PI3K-Akt-Gsk-3β pathway and subsequent inhibition of mPTP opening.…”
Section: Discussionmentioning
confidence: 99%